2015
DOI: 10.1111/asj.12392
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxisome proliferator‐activated receptor alpha in the expression of hepatic fatty acid oxidation‐related genes in chickens

Abstract: Liver is the most important target organ for investigation of lipid metabolism in domestic fowls. However, little is known about the regulatory mechanism of fatty acid oxidation in chicken liver. In mammals, proliferator-activated receptor alpha (PPARα), a transcription factor, plays an essential role in the regulation of hepatic fatty acid oxidation. The aim of the present study was to investigate the regulatory mechanisms of PPARα-induced gene expression involved in hepatic fatty acid oxidation in chickens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Although there are fewer studies investigating the links between PPAR and beta oxidation in chicken, there is indication that there are some similarities to other model organisms. In particular, carnitine palmitoyltransferase 1a ( CPT1A ) transcription seems to be regulated through PPARα (Honda et al 2016 ). Similar studies of PPAR-related effects of PFOS on the embryonic chicken liver have given varied responses, with studies in both 18 and 21 days chicken embryos indicating no significant changes to expression of PPAR-induced genes (O'Brien et al 2009 ; Strömqvist et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are fewer studies investigating the links between PPAR and beta oxidation in chicken, there is indication that there are some similarities to other model organisms. In particular, carnitine palmitoyltransferase 1a ( CPT1A ) transcription seems to be regulated through PPARα (Honda et al 2016 ). Similar studies of PPAR-related effects of PFOS on the embryonic chicken liver have given varied responses, with studies in both 18 and 21 days chicken embryos indicating no significant changes to expression of PPAR-induced genes (O'Brien et al 2009 ; Strömqvist et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…5A ). PPARα is a key transcription factor in promoting fatty acid betaoxidation [ 16 ]. To pursue this idea, we assessed mRNA expression involved in beta-oxidation including peroxisomal acyl-coenzyme A oxidase 1 (ACOX1), acyl-coenzyme A dehydrogenase for mediumchain fatty acids (AcadM), and acetyl-CoA carboxylase2 (ACC2), as well as mRNAs associated with TG degradation such as hormonesensitive lipase (HSL) and monoacylglycerol lipase (MGLL), and mRNAs that transport FFA into mitochondria such as carnitine palmitoyltransferase1 (CPT1) and CPT2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data revealed that activation of PPARα inhibited the expression of FASN and ACC, and lipid formation and cholesterol synthesis, which suggested that changes in lipid accumulation are caused by activity of PPARα through the regulation of FASN and ACC. Previous research studies showed that the PPARα agonist WY14643 effectively enhanced the expression of CPT-1α and ACO genes in chicken hepatoma cells, leading to the activation of the fatty acid oxidative pathway . Additionally, leucine stimulated milk synthesis in BMECs via PI3K-DDX59 signaling .…”
Section: Discussionmentioning
confidence: 99%